Evaluation of bread wheat (Triticum aestivum L.) genotypes for yield and related traits under drought stress conditions. (17th August 2020) - Semahegn, Yared; Shimelis, Hussein; Laing, Mark; Mathew, Isack
ABSTRACT: Drought is a major factor threatening crop production worldwide. Developing wheat varieties that are adapted to drought prone environments is a sustainable strategy to improve wheat production and productivity. The aim of this study was to evaluate and select bread wheat genotypes for yield and yield components, and for stability under drought stress and non-stress conditions. One hundred and twenty genotypes were evaluated at five test sites in the 2018/19 cropping season using a 10 x 12 alpha lattice design with two replicates. The level of drought stress was imposed using different sowing dates (early planting representing non-stressed, while late planting as drought stressed conditions) following the onset of the main rain at each site. Grain yield and yield components were recorded, and drought indices were calculated for each genotype. Among the drought tolerance indices, GMP, MP, HM, STI and YI were found to be the most suitable for predicting drought tolerance because they had significant and positive correlations with yield under drought stress and non-stress conditions. Rank sum analysis identified the most drought tolerant genotypes as 'YS-34', 'YS-85' and 'YS-82'. The selected wheat genotypes are useful genetic resources for future drought tolerance breeding programmes in Ethiopia or similar agro-ecologies.